X-ray absorption in the analysis of residual stresses in samples with cylindrical geometry - Vlasenko, Svetlana V.; Benediktovitch, Andrei I. (Journal of the Belarusian State University. Physics, 2017)
In this paper the influence of sample geometry on taking into account the X-ray absorption when passing through the sample is investigated. The paper deals with the case of cylindrical geometry. For this case the theoretical description of absorption in the samples with such a geometry is carried out. The obtained theoretical expressions were used for taking into account the absorption of X-rays in iron wires in the analysis of residual stresses. With the help of X-ray diffractometry diffraction profiles under various tilt and rotation angles of diffraction vector with respect to sample normal were obtained. The experimental profiles were fitted by the linear dependence since in this investigation the samples are supposed to be isotropic. On the basis of the results of fitting procedure the components of stress tensor were determined. It was established that there exist some deviations from linear dependence. It can be related to the presence of anisotropy of the sample because of texture or direction dependent grain interaction. It follows that for more rigorous description of the experimentally obtained dependencies it is necessary to consider the samples anisotropic and to supply the analysis of residual stresses with corresponding theory.
Keywords: X-ray diffractometry; absorption; residual stresses; cylindrical geometry; data fitting